2021
DOI: 10.1097/aud.0000000000000983
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Hearing Aids and Hearing Assistive Technology in a Working Population: Longitudinal Analyses of The Netherlands Longitudinal Study on Hearing

Abstract: Objective: To identify predictors of the 5-year uptake of hearing aids (HAs) and hearing assistive technology (HAT) in a sample of Dutch employees eligible for HAs and/or HAT. The potential predictors included demographic factors (age, sex, marital status, and living situation), education, hearing factors (ability to recognize speech in noise and self-reported hearing disability), distress, self-efficacy, and work-related factors (job demand, job control, and need for recovery). Design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Two studies reported mixed findings on speech recognition thresholds (SRTs) and their association with hearing aid uptake. Robertson et al (2012) found that people who purchased hearing aids had higher SRTs than those who did not purchase hearing aids, although van Leeuwen et al (2021) reported no association. The SRTs were measured for each ear using monitored live voice and the Central Institute for the Deaf W-1 spondaic word list ( Hirsh et al, 1952 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Two studies reported mixed findings on speech recognition thresholds (SRTs) and their association with hearing aid uptake. Robertson et al (2012) found that people who purchased hearing aids had higher SRTs than those who did not purchase hearing aids, although van Leeuwen et al (2021) reported no association. The SRTs were measured for each ear using monitored live voice and the Central Institute for the Deaf W-1 spondaic word list ( Hirsh et al, 1952 ).…”
Section: Resultsmentioning
confidence: 98%
“…Six studies reported a positive association between self-reported hearing disability and hearing aid uptake, although five studies reported no association. Five studies used various versions of the Hearing Handicap Inventory ( Fischer et al, 2011 ; Gopinath et al, 2011 ; Saunders et al, 2016 ; Simpson et al, 2019 ; Weycker et al, 2021 ) and one study used the Amsterdam Inventory for Auditory Disability and Handicap ( van Leeuwen et al, 2021 ). Two studies investigated hearing beliefs within the constructs of the HBM ( Saunders et al, 2016 , 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hearing assistive technologies (for instance, frequency modulation and loop systems, telecommunication devices, sign language interpretation, alerting devices and captioning services) have been developed to assist individuals who are hard of hearing (Crandell & Smaldino, 1999 ; Kricos, 2007 ; McPherson, 2014 ; Van Leeuwen et al, 2021 ). With the well-documented limited access to such technologies for large numbers in LMICs, lip-reading and sign language remain key to communication access for the hearing impaired and the deaf.…”
Section: Introductionmentioning
confidence: 99%